(untitled) (International Journal of Pathology, 2020)
Ḍiyāʾ Al-DīnAbūMuḥammadʿAbdllāh Ibn Aḥmad al-Mālaqī, commonly known as Ibn al-Bayṭār (Arabic: ابن البيطار‎) (1197–1248 AD) was an Andalusian Arabpharmacist, botanist, physician and scientist. His main contribution was to systematically record the additions made by Islamic physicians in the Middle Ages, which added between 300 and 400 types of medicine to the one thousand previously known since antiquity.[1] Ibn al-Baitar was born in the city of Málaga in Andalusia (Muslim-controlled Spain) at the end of the twelfth century, hence his nisba "al-Mālaqī".His name "Ibn al-Baitar" is Arabic for "son of the veterinarian", which was his father’s job. Ibn al-Bayṭār learned botany from the Málagan botanist Abū al-ʿAbbās al-Nabātī with whom he started collecting plants in and around Spain. Al-Nabātī was responsible for developing an early scientific method, introducing empirical and experimental techniques in the testing, description and identification of numerous materia medica, and separating unverified reports from those supported by actual tests and observations. Such an approach was thus adopted by Ibn al-Bayṭār